“Terusir dari Kampung Sendiri”: Political Ecology Study of Indigenous Communities Around Nickel Mining Project in central Halmahera - Andi Sumar Karman; Arlinah; Irfan Ahmad (International Journal of Applied and Scientific Research, 2024)
The complexity of problems caused by mining activities in North Maluku can be analyzed through the perspective of political ecology from anthropology, especially ecological anthropology. Through this perspective, the article describes three main problems related to mining business activities in relation to the conditions of indigenous communities around the mines. First, about the environmental perception of indigenous communities towards nickel mining activities in Central Halmahera Regency. Second, regarding the power gap and social injustice due to nickel mining activities towards local communities in Central Halmahera. Third, regarding access to natural resources and the marginalization of local communities in the context of the utilization of natural mining resources. The presence of nickel mining companies in Central Halmahera Regency does not have a positive impact on the lives of indigenous people living around mining activities. Their natural environment is damaged (polluted) and the main sources of livelihood of indigenous people are lost from their control. They no longer have access to the natural resources that they previously controlled before the arrival of the nickel mining company.